Mixed magnetic behavior in gadolinium and ruthenium co-doped nickel oxide nanoparticles. (10th January 2022) - Abdallah, A M; Awad, R
Abstract: Pure and different concentrations from (Gd, Ru) co-doped NiO nanoparticles, capped with Polyvinylpyrrolidone (PVP), were fabricated by the co-precipitation method. The nanoparticles were characterized by different techniques. The Rietveld refinements of x-ray Diffraction (XRD) patterns confirmed the formation of the pure face-centered-cubic NiO phase. The x-ray Photo-induced Spectroscopy (XPS) assured the trivalent oxidation state of the doped ions Gd 3+ and Ru 3+ and unveiled the multiple oxidation states of nickel ions (Ni 2+ and Ni 3+ ), emerging from the vacancies in the samples. The Transmission Electron Microscope (TEM) images showed the pseudospherical morphology of the samples and the Energy Dispersive x-ray permitted the quantitative analysis of the presented elements and their homogeneous distribution. The Raman and Fourier Transform Infra-Red (FTIR) spectra depicted the fundamental vibrational bands of NiO nanoparticles, confirming their purity. The UV-visible spectroscopy enabled the absorption measurements and the energy gap calculations. The co-dopants increased the energy bandgap of NiO nanoparticles from 3.15 eV for pure NiO to 3.62 eV with the highest concentration of the co-dopants ( x = 0.02) The photoluminescence (PL) spectra gave insights into the possible defects present in the samples, such as nickel vacancies, single and double oxygen vacancies, and oxygen interstitials. The Vibrating Sample Magnetometer (VSM) studied the room temperature M-H loops of the co-doped samples. A combination of ferromagnetic, antiferromagnetic, and paramagnetic contributions was noticed and treated according to the law of approach to saturation and bound magnetic polaron (BMP) model. The magnetic parameters, such as the saturation magnetization, exchange and anisotropy field, and the BMP concentration were extracted from the fitted models and discussed in terms of the co-dopants' concentration. The co-doped samples showed a softer magnetic behavior, which is recommended for data storage applications.